HUBUNGAN PENGETAHUAN IBU TENTANG ALAT KONTRASEPSI KB SUNTIK DENGAN TERJADINYA PENAMBAHAN BERAT BADAN IDEAL IBU DI DI POLINDES PONJANAN - Susia Yulianti; Yayuk Eliyana (Universitas Islam Madura, 2021)
One attempt to tackle the population problem is to follow the family planning program intended to help couples and individuals in reproductive health, prevent unwanted pregnancies and reduce the incidence of high-risk pregnancy, illness and death, making service quality, affordable, acceptable and easily available to everyone in need, improve the quality of advice, communication, education, counseling and services improve health. This study aims is to analyze the mother's knowledge about contraception KB syringe with the ideal maternal weight gain in the working area of ​​the health center Polindes Ponjanan Batumarmar Pamekasan. This study is the type used is the Analytic Correlation is a research study to find the facts and the correct interpretation of test results processed with statistical sampling using probability sampling methods with the type of simple random sampling as many as 69 people. As a variable in this study is the mother of knowledge about birth control injections with the addition of ideal body weight. Data is collected using a questionnaire, then the data analyzed in the frequency table for each variable, followed by using Spearman correlation test. Based on the results of a study of 69 mothers data showed that most mothers who have poor knowledge about contraception as much as 46,38% KB injection, while those experiencing weight gain as much as 69,57%. From these results we can conclude that there is a relationship between maternal knowledge about contraception KB syringe with weight gain in the working area of ​​the village health center Ponjanan Batumarmar Pamekasan 2012. The correlation of test results analisia Spearmans probability values ​​obtained 0.00 <0.05 where Ho is rejected and Ha accepted .. Of the value of the correlation coefficient of -0.677, which means a strong influence in a negative correlation. From these results we can conclude that that means there is a relationship of maternal knowledge tengant KB injectable contraceptives with the addition of ideal body weight. This is because most of the respondents had primary school education level and employment are owned by the housewife. Efforts to do is to education about the benefits and usefulness of contraceptives as well as the negative impact that can be caused by the use of a syringe contraception KB.